Evolutionary‐Distinct Viral Proteins Subvert Rice Broad‐Spectrum Antiviral Immunity Mediated by the RAV15‐MYC2 Module - Hehong Zhang; Chaorui Huang; Chenfei Gao; Wenkai Yan; Weiqi Song; Xiaodi Hu; Lulu Li; Zhongyan Wei; Yanjun Li; Jianping Chen; Zongtao Sun (Advanced Science)
Abstract A variety of plant viruses employ different virulence strategies to achieve successful infection, resulting in abnormal plant development. However, the common pathogenicity of distinct viruses has rarely been studied. Here, it is shown that a plant‐specific RAV‐type transcription factor, OsRAV15, is specifically targeted by several distinct viral proteins for facilitating viral infection. OsRAV15 is found to activate jasmonic acid (JA)‐mediated broad‐spectrum antiviral immunity by physically associating with JA signaling essential components OsMYC2‐OsJAZ complex. To facilitate viral infection, evolutionarily distinct viral proteins encoded by diverse rice viruses generally disrupt the OsRAV15‐OsMYC2 complex to attenuate activation of JA signaling. Together, the results reveal a common counter‐defense strategy used by different viruses to suppress the OsRAV15‐OsMYC2 module that plays a vital role in fine‐tuning JA‐mediated antiviral defense.